The Role of Quality, Promotion, and Product Uniqueness in the Decision-Making to Purchase Batik Gayatri - Prabawanti, Benedicta Evienia; Ramawati, Yussi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Batik is a valued cultural heritage of Indonesia, loved by both domestic and foreign tourists. The batik industry is growing, leading to tough competition. Producers need to enhance quality, promotion, and appeal to attract customers. New players are entering the market, so Batik Gayatri must innovate to stay successful in the fashion industry. This research aims to determine the influence of product quality, promotion, and uniqueness on Batik Gayatri's purchasing decisions. Product quality is one of the factors that shows durability, reliability, and other valuable attributes of a product. Promotion is a marketing tool that every business actor must have. Promotion can be done in various ways, including using social media and digital technology to carry out promotions. The product's unique features need to be consistently emphasized to both current and potential customers. The uniqueness of the product gives an idea of the various innovations made by Batik Gayatri in the fashion sector. This research uses quantitative methods, which are analyzed using SEM-PLS to determine the influence of quality, promotion, and product uniqueness on purchasing decisions for Batik Gayatri. Research respondents are consumers who buy and use Batik Gayatri products. Data and information collection for research purposes was carried out through interviews and distributing questionnaires. The research results show that only product uniqueness significantly affects purchasing decisions, while product quality and promotion do not directly influence purchasing decisions. Apart from that, the uniqueness of the product and quality through product promotion is also insignificant in consumer purchasing decisions.